Advanced topics in computer vision - Farinella, Giovanni Maria; Battiato, Sebastiano; Cipolla, Roberto (London Springer, 2013)
Computer vision is the science and technology of making machines that see. It is concerned with the theory, design and implementation of algorithms that can automatically process visual data to recognize objects, track and recover their shape and spatial layout.? This unique text/reference presents a broad selection of cutting-edge research, covering both theoretical and practical aspects of the three main areas in computer vision: reconstruction, registration, and recognition. The book provides an in-depth overview of challenging areas, in addition to descriptions of novel algorithms that exploit machine learning and pattern recognition techniques to infer the semantic content of images and videos.
Includes bibliographical references and index.
E2-641G donated by Mr. Johnson Apacible.
Keywords: Computer vision; Artificial intelligence; Pattern recognition systems